(untitled) (Applied Biological Research, 2024)
This study was conducted at Lahore Zoo, Punjab, Pakistan from January to December 2023 to assess the prevalence of gastrointestinal parasites in 10 different captive wild mammalian species. The mammals including girrafe (Giraffa), vervet monkey (Chlorocebus pygerythrus), zebra (Equus quagga), lion (Panthera leo), leopard (Panthera pardus), Rhinoceros (Rhinocerotidae), wild boar (Sus scrofa), Chinkara deer (Gazella bennettii), urial (Ovis vignei) and nilgai (Boselaphus tragocamelus) were selected. A total of 100 fresh fecal samples were collected from the animal enclosures in polythene bags (6×4 inches) 2 times during study period. Coprological examination was done using qualitative analysis such as direct smear method, sedimentation method and flotation methods. The parasitic prevalence was as follows zebra 44.5%, followed by giraffes, rhinoceroses, and wild boars at 27.8%, nilgai, urial, lion and vervet monkey at 22.3%, chinkara 16.7% and leopard 11.2%. The prevalence of gastrointestinal parasites was as Eimeria spp. (3.9%), Strongyloides spp. (3.4%), Trichuris spp. (2.8%), Giardia spp., Ascaris spp., and Strongyle spp. (2.3%), Entamoeba histolytica (1.12%), Trematode eggs (1.12%), Nematodirus (1.12%), Balantidium coli (0.6%), Haemonchus contortus (0.6%), Paramphistomum cervi (0.6%), Parascaris equorum (1.12%) and Cryptosporidium (1.12%). The overall parasitic prevalence was 23.9%, with a noticeable seasonal variation, being higher in summer (31.2%) compared to winter (17.79%). These findings highlight the significant parasitic burden in captive wild mammals. It can be concluded that regular de-worming sessions, cleaning, disinfection of enclosures and proper disposal of fecal matter should be done to reduce the overall parasitic burden.